The perspectives of Aboriginal patients and their health care providers on improving the quality of hemodialysis services: A qualitative study - Rix, Elizabeth F (Hemodial Int, 2015)
Chronic kidney disease has a higher prevalence in Indigenous populations globally. The incidence of end-stage kidney disease in Australian Aboriginal people is eight times higher than non-Aboriginal Australians. Providing services to rural and remote Aboriginal people with chronic disease is challenging because of access and cultural differences. This study aims to describe and analyze the perspectives of Aboriginal patients' and health care providers' experience of renal services, to inform service improvement for rural Aboriginal hemodialysis patients. We conducted a thematic analysis of interviews with Aboriginal patients (n = 18) receiving hemodialysis in rural Australia and health care providers involved in their care (n = 29). An overarching theme of avoiding the “costly” crisis encompassed four subthemes: (1) Engaging patients earlier (prevent late diagnosis, slow disease progression); (2) flexible family-focused care (early engagement of family, flexibility to facilitate family and cultural obligations); (3) managing fear of mainstream services (originating in family dialysis experiences and previous racism when engaging with government organizations); (4) service provision shaped by culture (increased home dialysis, Aboriginal support and Aboriginal-led cultural education). Patients and health care providers believe service redesign is required to meet the needs of Aboriginal hemodialysis patients. Participants identified early screening and improving the relationship of Aboriginal people with health systems would reduce crisis entry to hemodialysis. These strategies alongside improving the cultural competence of staff would reduce patients' fear of mainstream services, decrease the current emotional and family costs of care, and increase efficiency of health expenditure on a challenging and increasingly unsustainable treatment system.